Randomly polarised beam produced by magnetooptically Q-switched laser. Issue 1 (December 2017) - Morimoto, Ryohei; Goto, Taichi; Taira, Takunori; Pritchard, John; Mina, Mani; Takagi, Hiroyuki; Nakamura, Yuichi; Lim, Pang; Uchida, Hironaga; Inoue, Mitsuteru
Abstract Diode-pumped solid-state micro lasers are compact (centimetre-scale), highly stable, and efficient. Previously, we reported Q-switched lasers incorporating rare-earth substituted iron garnet (RIG) film. Here, the first demonstration of the magnetooptical (MO) Q-switch in an Nd:YAG laser cavity is performed. We fabricate a quasi-continuous-wave (QCW) diode-pumped Nd:YAG laser cavity, which is shortened to 10 mm in length and which contains an RIG film and a pair of small coils. This cavity yields a 1, 064.58-nm-wavelength pulse with 25-ns duration and 1.1-kW peak power at a 1-kHz repetition ratio. Further, the polarisation state is random, due to the isotropic crystal structure of Nd:YAG and the fact that the MO Q-switch incorporating the RIG film does not require the presence of polarisers in the cavity. This is also the first report of an MO Q-switch producing random polarisation.